The water resistance of a recycled base with foamed bitumen in the aspect of road binder composition - Przemysław Buczyński; Marek Iwański; Grzegorz Mazurek (Budownictwo i Architektura, 2016)
The paper describes research results of recycled base which was performed in a cold deep recycling technology with foamed bitumen and different type of hydraulic mixed binder in the aspect of water resistance. An individual design of a composition of a binder enables to achieve a precise adjustment of a binder’s impact to local conditions and required parameters of a recycled base. The design a recycled base with foamed bitumen simulated a cold deep recycling process with materials from existing crushed bituminous pavement layers ("technology in-situ"). To produce the foamed bitumen a road bitumen of penetration grade 50/70 was used. Moreover, the following mineral components were categorised as a waste material: reclaimed asphalt pavement, 0/31,5 mm aggregate and aggregates for soil gradation improvement 0/4. A composition of the recycled base consisted of the binders prepared in the laboratory as a result of a mix of three basic components. The percentage of individual road binders was determined in line with the plan of the simlex-centroid experiment. For the purpose of determining an influence of such a hydraulic road binder on the water resistance in recycled base, the following tests were carried out: void contents Vm, tensile strength ratio TSR (water resistance). Additionally, an evaluation of increase of indirect tensile modulus (IT-CY) was conducted. On the basis of the test results, a varied impacts of tested hydraulic road binders on mechanical properties and water resistence of recycled base with foamed bitumen were observed. On the basis of the plan of the experiment, it was possible to determine the recommended road binder composition that enabled to obtain the water resistance in the recycled base with foamed bitumen